Kinetics of carbon monoxide binding to phenobarbital-induced cytochrome P-450 from rat liver microsomes: a simple bimolecular process. - Oertle, M (1985)
The kinetics of carbon monoxide binding to phenobarbital-induced cytochrome P-450 (P-450PB) and to its enzymatically inactive form P-420PB have been investigated by both stopped-flow and flash-photolysis spectrophotometry. When the simultaneous presence of both forms of the enzyme is taken into account, the binding of CO to these two proteins can be described in terms of two bimolecular processes with rate constants of 4.5 X 10(6) M-1.S-1 and 4.7 X 10(5) M-1.S-1 for P-450PB and 1.7 X 10(7) M-1.S-1 and 1.5 X 10(6) M-1.S-1 for P-420PB. From kinetic studies of the binding of CO to P-450PB under different experimental conditions, investigations of the homogeneity of our P-450PB preparations, and comparative kinetic investigations of P-450s from different sources, we conclude that CO binding to reduced P-450PB is a simple bimolecular process and that the observed biphasic traces are due to heterogeneity of the proteins. This conclusion is in contrast with previous reports of complex reaction mechanisms for the binding of CO to P-450PB. Optical spectroscopy studies indicate the existence of an equilibrium between P-450PB and P-420PB, at least for the reduced carbonyl derivatives of the enzymes. The interconversion is strongly influenced by the aggregation state of the protein. Large differences between the CO binding properties of P-450PB and those of P-420PB are found. These are discussed in terms of possible effects of the proximal ligation state of the iron on heme reactivity.